New Technology of Preparing Barium Carbonate by Two Transformations of Barite in Liquid Phase - Xiangbi WANG; Junhong ZHOU; Lei MA; Haiyan LI; Weiling HAN; Zongjing WAN (Kuangchan zonghe liyong, 2024)
This is an article in the field of metallurgical engineering. Aiming at the limitation of low reactivity of barite and few chemical processing methods, a new soda ash conversion method is proposed. Firstly, the effect of barite reaction particle size, temperature, and sodium carbonate concentration on the production rate of barium carbonate by the hydrochloric acid hydrolysis method is explored. The results show that the sodium carbonate concentration has the greatest impact on the reaction conversion rate. At limited experimental conditions, when sodium carbonate is used when the concentration reaches 28.57%, the highest formation rate of barium carbonate reaches 90.05%. Secondly, in the subsequent reaction, ammonium chloride is selected to re-convert the barite conversion product to prepare ammonium carbonate. The barium carbonate produced by this method has a higher yield and purity. The new process breaks through the traditional misconception that barium sulfate does not react with soda ash. The process is simple and feasible, and ammonia and carbon dioxide can be recycled and reused, making the entire process a large cycle process, in line with the concept of green environmental protection, and recrystallization. The preparation of barium carbonate from stone provides a new production process.